Psychosocial reintegration post-traumatic spinal cord injury in Rwanda: An exploratory study - Maurice Kanyoni; Lena N. Wikmar; Joliana Philips; David K. Tumusiime (AOSIS, 2024)
Background: Traumatic spinal cord injury (TSCI) survivors are confronted by both physical and psychosocial barriers when returning to their communities. Therefore, reintegration is an important aspect of their journey back into social life. Objectives: To assess psychosocial reintegration after TSCI in Rwanda. Method: All community-dwelling adults who were registered in the previous epidemiological study were recruited and injury characteristics questionnaire and the Sydney Psychosocial Reintegration Scale version 2 (SPRS-2) were used to collect data through a telephone interview. Results: The study traced 58 participants, 77.6% (n = 45) were male and 56.9% (n = 33) were categorised with paraplegia. Overall, the results show poor community reintegration. The SPRS-2 and domain mean (SD) scores were: overall SPRS-2 of 20.95 (11.56), occupational activity (OA) of 3.68 (4.31), interpersonal relationship (IR) of 7.11(4.31) and living skills (LS) of 7.43 (5.32). Gender significantly influenced overall SPRS-2 (p = 0.011) and two domains: OA (p = 0.005) and LS (p = 0.012). Level of injury was significantly associated with an OA domain score of SPRS-2 (p = 0.002). Gender explained 29% of the variance in the LS domain of SPRS-2, with males reporting better psychosocial reintegration. Conclusion: Gender strongly predicted psychosocial reintegration following a TSCI, which is an indication of the role of social support. Clinical Implications: Traumatic SCI rehabilitation should be holistic to help prepare the person to return to the community. There should be an assessment of an individual's readiness to return to the community before discharge from the hospital.